Planck early results: IV. First assessment of the high frequency Instrument in-flight performance - Ade, Peter A.; Bartelmann, Matthias; Schäfer, Björn Malte (Arxiv, 2011)
The Planck High Frequency Instrument (HFI) is designed to measure the temperature and polarization anisotropies of the Cosmic Microwave Background and galactic foregrounds in six wide bands centered at 100, 143, 217, 353, 545 and 857 GHz at an angular resolution of 10' (100 GHz), 7' (143 GHz), and 5' (217 GHz and higher). HFI has been operating flawlessly since launch on 14 May 2009. The bolometers cooled to 100 mK as planned. The settings of the readout electronics, such as the bolometer bias current, that optimize HFI's noise performance on orbit are nearly the same as the ones chosen during ground testing. Observations of Mars, Jupiter, and Saturn verified both the optical system and the time response of the detection chains. The optical beams are close to predictions from physical optics modeling. The time response of the detection chains is close to pre-launch measurements. The detectors suffer from an unexpected high flux of cosmic rays related to low solar activity. Due to the redundancy of Planck's observations strategy, the removal of a few percent of data contaminated by glitches does not affect significantly the sensitivity. The cosmic rays heat up significantly the bolometer plate and the modulation on periods of days to months of the heat load creates a common drift of all bolometer signals which do not affect the scientific capabilities. Only the high energy cosmic rays showers induce inhomogeneous heating which is a probable source of low frequency noise.
Gesehen am 22.09.2017